Sealing glass powder with low dielectric constant and dielectric loss and preparation method thereof

By reasonably preparing borosilicate glass powder and silica powder in the sealing glass powder, the content of alkali metal oxides is controlled, the problem of high dielectric constant of existing sealing glass materials is solved, and the effect of low dielectric constant and dielectric loss is achieved, the preparation process is simplified and energy consumption is reduced.

CN119569346AInactive Publication Date: 2025-03-07HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411790963.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sealing glass materials have a high dielectric constant, which is difficult to reach below 5, and the preparation process is complex and energy consumption is high, which affects its application in the electronics field.

Method used

Seal glass powder with low dielectric constant and dielectric loss is adopted, and its components include 80% to 100% borosilicate glass powder and 0% to 20% silica powder. Through specific formulations and preparation methods, the content of alkali metal oxides is controlled to reduce the dielectric constant and dielectric loss of the glass.

Benefits of technology

It realizes the low dielectric constant and dielectric loss of sealing glass powder, reduces the sealing temperature, simplifies the preparation process, reduces production energy consumption, is suitable for large-scale production, and is suitable for electronic packaging and electrical connector sealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569346A_ABST
    Figure CN119569346A_ABST
Patent Text Reader

Abstract

The invention discloses sealing glass powder with low dielectric constant and dielectric loss and a preparation method thereof, and belongs to the field of preparation of borosilicate glass and special glass. The sealing glass powder comprises the following components in percentage by mass: 80-100% of borosilicate glass powder and 0-20% of silicon dioxide powder; the borosilicate glass powder is prepared from the following components in percentage by mass: 56 percent to 65 percent of SiO2, 26 percent to 40 percent of B2O3, 0 percent to 2 percent of Al2O3, 0 percent to 2 percent of ZnO, 2 percent to 3 percent of Li2O, 0 percent to 1.5 percent of Na2O, 0 percent to 1.5 percent of K2O, 0.5 percent to 1 percent of Cr2O3, 0 percent to 0.5 percent of BaO and 0 percent to 0.5 percent of CaF2. The dielectric constant and dielectric loss of the material are reduced, and the dielectric property of the sealing glass powder is improved. The sealing glass powder is low in sealing temperature, simple in preparation method, low in production energy consumption, easy to control and suitable for electronic packaging and sealing of electric connectors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of borosilicate glass and special glass preparation, and relates to a sealing glass powder with low dielectric constant and dielectric loss and a preparation method thereof. Background Art

[0002] Sealing glass powder is an inorganic adhesive that can achieve mutual connection between ceramic-ceramic, metal-metal, and ceramic-metal. In addition to the connection function, sealing glass is also required to have good airtightness and electrical insulation between the connected parts. Sealing glass is often used for sealing high-precision devices or electronic components. With the development of the electronics field, people have higher and higher requirements for the packaging of semiconductor components and high-frequency signal transmission electrical connectors. Therefore, the requirements for the dielectric properties of sealing glass are also getting higher and higher. The dielectric properties of glass have become one of the important indicators that determine its application in the electronics field. Low dielectric constant can reduce signal relaxation and cross-interference, and low dielectric loss can reduce energy loss at high frequencies. The dielectric constant of existing sealing glass materials is generally around 5. To achieve a dielectric constant of less than 5, around 4, a higher melting temperature is usually required, and the preparation of glass materials is more difficult. Therefore, it is imperative to develop sealing glass materials with low dielectric constant and low dielectric loss. SiO2 and B2O3 have the lowest dielectric constants among all oxides and are the network forming components of glass, which to a certain extent determine the dielectric properties of glass. Among them, too much SiO2 will make the glass difficult to melt, thereby increasing the difficulty and energy consumption of melting. Summary of the invention

[0003] The purpose of the present invention is to solve the problem of poor dielectric properties of sealing glass and provide a sealing glass powder with low dielectric constant and dielectric loss and a preparation method thereof.

[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0005] A sealing glass powder with low dielectric constant and dielectric loss, the sealing glass powder comprising 80% to 100% borosilicate glass powder and 0% to 20% silicon dioxide powder in terms of mass percentage; the borosilicate glass powder comprising 56% to 65% SiO2, 26% to 40% B2O3, 0% to 2% Al2O3, 0% to 2% ZnO, 2% to 3% Li2O, 0% to 1.5% Na2O, 0% to 1.5% K2O, 0.5% to 1% Cr2O3, 0% to 0.5% BaO and 0% to 0.5% CaF2 in terms of mass percentage.

[0006] Alkali metal oxides (Li2O, Na2O, K2O) can greatly reduce the viscosity of glass liquid, and are flux for making glass, which have a great influence on the formation of glass and the clarification process of glass liquid. However, if the content of alkali metal oxides is too much, the chemical stability, thermal stability and mechanical strength of the glass will be greatly reduced. The increase of alkali metal oxides will convert part of the bridging oxygen in the glass into non-bridging oxygen, destroying the compactness of the glass network structure, thereby increasing the dielectric constant and dielectric loss of the glass. Therefore, the content of alkali metal oxides needs to be strictly controlled. The content of alkali metal oxides in the borosilicate glass powder of the present invention is 2% to 6%, preferably 2% to 3%.

[0007] A method for preparing the above-mentioned sealing glass powder with low dielectric constant and dielectric loss, the method comprising:

[0008] (1) Mix and grind all the raw materials of borosilicate glass powder in a mortar until they are uniformly mixed;

[0009] (2) placing the mixed raw materials in a corundum crucible, placing the corundum crucible in a muffle furnace and keeping the temperature at 1500-1550° C. for 1-2 hours, pouring the molten glass into a double-roll cold rolling mill to obtain a glass sheet;

[0010] (3) Place the glass piece in a sealed sample preparation crusher and crush it for 1 to 2 minutes to obtain a coarse glass powder;

[0011] (4) 80% to 100% coarse glass powder and 0% to 20% silica powder are mixed uniformly in a mortar, ethanol is added, and the mixture is placed in a ball mill. The mixture is fully mixed and ball milled at a speed of 500 rpm for 3 hours. The ball-milled glass powder is placed in an oven and dried at 80° C. for 24 hours to obtain dry glass fine powder, i.e., the sealing glass powder of the present invention.

[0012] Furthermore, in step (4), the mass ratio of powder to zirconium oxide balls and anhydrous ethanol is 1:4:4.

[0013] The beneficial effects of the present invention over the prior art are as follows: the present invention adds an appropriate amount of silicon dioxide powder to the prepared borosilicate glass powder, thereby reducing the dielectric constant and dielectric loss of the material and improving the dielectric properties of the sealing glass powder. The sealing glass powder has a low sealing temperature, a simple preparation method, low production energy consumption, is easy to control, is suitable for large-scale production, is suitable for electronic packaging and the sealing of electrical connectors, and provides a new idea for improving the dielectric properties of the sealing glass powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a dielectric constant diagram obtained in Examples 1 to 4;

[0015] Figure 2 is a dielectric constant diagram obtained in Examples 5 to 8;

[0016] Figure 3 is the dielectric loss diagram obtained in Examples 1 to 4;

[0017] Figure 4 is the dielectric loss diagram obtained in Examples 5 to 8;

[0018] Figure 5 This is a photo of the insulator sealed with glass powder according to the invention. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific implementation methods. It should be understood that the specific implementation methods described here are only used to explain the present invention and do not limit the scope of protection of the present invention.

[0020] SiO2 is an important network former of glass, with silicon-oxygen tetrahedron [SiO4] as the structural unit. It is the main substance for forming glass and the basis for forming glass. It can reduce the crystallization tendency of glass and improve the chemical stability, mechanical strength and thermal stability of glass. SiO2 has good dielectric properties and can reduce the dielectric constant of glass. When the content of SiO2 exceeds 70%, the glass is difficult to melt, the viscosity of the molten glass liquid is large and the fluidity is poor, and it is difficult to melt. The content of SiO2 in the borosilicate glass powder of the present invention is 56% to 65%.

[0021] B2O3 is a network former that constitutes glass, with boron-oxygen triangle [BO3] and boron-oxygen tetrahedron [BO4] as structural units, and together with silicon-oxygen tetrahedron in borosilicate glass, it forms a structural network. B2O3 acts as a flux at high temperatures, which can reduce the viscosity of the glass liquid and accelerate the melting of the glass. B2O3 can reduce the dielectric constant of the glass. If the B2O3 content is low, the relative dielectric constant is difficult to meet the design requirements. If the B2O3 content exceeds 40%, the chemical stability of the glass decreases and the water resistance deteriorates. The content of B2O3 in the borosilicate glass powder of the present invention is 26% to 40%.

[0022] Al2O3 is an intermediate oxide of glass, which can reconnect broken silicon-oxygen tetrahedrons [SiO4] to make the structure of glass more stable, thereby improving the dielectric properties of the material. Introducing an appropriate amount of Al2O3 into the glass composition can reduce the crystallization tendency of the glass, improve chemical stability and mechanical strength. When the Al2O3 content is too high, it will increase the high-temperature viscosity of the glass and also affect the dielectric properties of the glass. The content of Al2O3 in the borosilicate glass powder of the present invention is 0% to 2%.

[0023] ZnO is an intermediate oxide of glass, which can reduce the high temperature viscosity of glass and play a good role in fluxing. ZnO can increase the transparency, brightness, tensile deformation resistance and corrosion resistance of glass. When the ZnO content is too high, the dielectric constant of glass will be increased, which will affect the dielectric properties of glass. The content of ZnO in the borosilicate glass powder of the present invention is 0% to 2%.

[0024] Cr2O3 plays a role in coloring the glass, which has a good aesthetic effect. At the same time, Cr2O3 also improves the chemical stability of the glass and prevents the glass from being corroded by water and causing negative effects such as corrosion. The effect of a small amount of Cr2O3 on the performance of the glass can be ignored, but when the content of Cr2O3 is too much, it will have a greater impact on the performance of the glass. The content of Cr2O3 in the borosilicate glass powder of the present invention is 0.5% to 1%.

[0025] BaO is a divalent network exometallic oxide in glass, which can improve the chemical stability and mechanical strength of glass. However, the introduction of BaO will increase the dielectric constant of glass, so the content of alkaline earth metal oxides such as BaO needs to be strictly controlled. The content of BaO in the borosilicate glass powder of the present invention is 0% to 0.5%.

[0026] CaF2 can enhance the hardness of glass, improve its wear resistance and corrosion resistance, and fluoride plays a role in melting and clarifying glass, which can accelerate the melting of glass. However, excessive addition will deteriorate the stability of glass. The content of CaF2 in the borosilicate glass powder of the present invention is 0% to 0.5%.

[0027] The synergistic effects of the above raw materials of the present invention are as follows:

[0028] 1. Alkali metal oxides (Li2O, Na2O, K2O) and B2O3: Alkali metal oxides (Li2O, Na2O, K2O) provide some free oxygen, which combines with some boron oxygen triangles [BO3] in B2O3 to transform into boron oxygen tetrahedrons [BO4], changing the structure of boron from layered to frame, making the glass structure compact.

[0029] 2. SiO2 and intermediate oxides (ZnO, Al2O3): The intermediate oxides (ZnO, Al2O3) reconnect with some silicon-oxygen tetrahedrons in SiO2 that were broken by alkali metal oxides, making the silicon-oxygen tetrahedron structure of the glass more stable.

[0030] 3. Mixed alkali effect: A mixed alkali effect occurs between alkali metal oxides (Li2O, Na2O, K2O). The dielectric constant and dielectric loss of glass containing mixed alkali metals are generally lower than those of single alkali metal glass, and the stability of mixed alkali glass is better than that of single alkali glass.

[0031] Example 1

[0032] (1) The following raw materials in weight percentage are mixed and ground uniformly in a mortar: 65% SiO2, 30% B2O3, 0.5% Al2O3, 0% ZnO, 2.5% Li2O, 0.5% Na2O, 0.5% K2O, 0.5% Cr2O3, 0.4% BaO, and 0.1% CaF2.

[0033] (2) The mixed glass raw materials are placed in a corundum crucible, the corundum crucible is sent into a muffle furnace and kept at 1550° C. for 2 h, and the molten glass liquid is poured into a double-roll cold rolling mill to obtain a glass sheet.

[0034] (3) Place the glass piece in a sealed sample preparation crusher and crush it for 1 minute to obtain coarse glass powder.

[0035] (4) Mix 100% glass coarse powder and 0% silica powder in a mortar, and put them into a ball mill. The mass ratio of the powder to zirconium oxide balls and anhydrous ethanol is 1:4:4. The mixture is fully mixed and ball milled at a speed of 500 rpm for 3 hours. The ball-milled glass powder is placed in an oven and dried at 80°C for 24 hours to obtain dry glass fine powder, i.e., the sealing glass powder of the present invention.

[0036] Example 2

[0037] (1) The following raw materials in weight percentage are mixed and ground uniformly in a mortar: 65% SiO2, 28% B2O3, 1.5% Al2O3, 0.5% ZnO, 2% Li2O, 1% Na2O, 1% K2O, 0.5% Cr2O3, 0.4% BaO, and 0.1% CaF2.

[0038] (2) The mixed glass raw materials are placed in a corundum crucible, the corundum crucible is sent into a muffle furnace and kept at 1550° C. for 1 hour, and the molten glass liquid is poured into a double-roll cold rolling mill to obtain a glass sheet.

[0039] (3) Place the glass piece in a sealed sample preparation crusher and crush it for 1 minute to obtain coarse glass powder.

[0040] (4) 95% by mass of coarse glass powder and 5% by mass of silica powder were mixed evenly in a mortar, and then placed in a ball mill with a mass ratio of powder to zirconium oxide balls and anhydrous ethanol of 1:4:4. The mixture was fully mixed and ball milled at a speed of 500 rpm for 3 hours. The ball-milled glass powder was placed in an oven and dried at 80°C for 24 hours to obtain dry glass fine powder, i.e., the sealing glass powder of the present invention.

[0041] Example 3

[0042] (1) The following raw materials in weight percentage are mixed and ground uniformly in a mortar: 65% SiO2, 28% B2O3, 2% Al2O3, 1% ZnO, 3% Li2O, 0% Na2O, 0% K2O, 0.5% Cr2O3, 0.4% BaO, and 0.1% CaF2.

[0043] (2) The mixed glass raw materials are placed in a corundum crucible, the corundum crucible is sent into a muffle furnace and kept at 1550° C. for 1 hour, and the molten glass liquid is poured into a double-roll cold rolling mill to obtain a glass sheet.

[0044] (3) Place the glass piece in a sealed sample preparation crusher and crush it for 1 minute to obtain coarse glass powder.

[0045] (4) 90% by mass of coarse glass powder and 10% by mass of silica powder were mixed evenly in a mortar, and the mixture was placed in a ball mill with a mass ratio of powder to zirconium oxide balls and anhydrous ethanol of 1:4:4. The mixture was fully mixed and ball milled at a speed of 500 rpm for 3 hours. The ball-milled glass powder was placed in an oven and dried at 80°C for 24 hours to obtain dry glass fine powder, i.e., the sealing glass powder of the present invention.

[0046] Example 4

[0047] (1) The following raw materials in weight percentage are mixed and ground uniformly in a mortar: 65% SiO2, 28% B2O3, 1.5% Al2O3, 0.5% ZnO, 2% Li2O, 1% Na2O, 1% K2O, 0.5% Cr2O3, 0.4% BaO, and 0.1% CaF2.

[0048] (2) The mixed glass raw materials are placed in a corundum crucible, the corundum crucible is sent into a muffle furnace and kept at 1550° C. for 1 hour, and the molten glass liquid is poured into a double-roll cold rolling mill to obtain a glass sheet.

[0049] (3) Place the glass piece in a sealed sample preparation crusher and crush it for 1 minute to obtain coarse glass powder.

[0050] (4) 85% by mass of coarse glass powder and 15% by mass of silica powder were mixed evenly in a mortar, and the mixture was placed in a ball mill with a mass ratio of powder to zirconium oxide balls and anhydrous ethanol being 1:4:4. The mixture was fully mixed and ball milled at a speed of 500 rpm for 3 hours. The ball-milled glass powder was placed in an oven and dried at 80°C for 24 hours to obtain dry glass fine powder, i.e., the sealing glass powder of the present invention.

[0051] Example 5

[0052] (1) The following raw materials in weight percentage are mixed and ground uniformly in a mortar: 65% SiO2, 28% B2O3, 1.5% Al2O3, 0.5% ZnO, 2% Li2O, 1% Na2O, 1% K2O, 0.5% Cr2O3, 0.4% BaO, and 0.1% CaF2.

[0053] (2) The mixed glass raw materials are placed in a corundum crucible, the corundum crucible is sent into a muffle furnace and kept at 1550° C. for 1 hour, and the molten glass liquid is poured into a double-roll cold rolling mill to obtain a glass sheet.

[0054] (3) Place the glass piece in a sealed sample preparation crusher and crush it for 1 minute to obtain coarse glass powder.

[0055] (4) 80% by mass of coarse glass powder and 20% by mass of silica powder were mixed evenly in a mortar, and the mixture was placed in a ball mill with a mass ratio of powder to zirconium oxide balls and anhydrous ethanol of 1:4:4. The mixture was fully mixed and ball milled at a speed of 500 rpm for 3 hours. The ball-milled glass powder was placed in an oven and dried at 80°C for 24 hours to obtain dry glass fine powder, i.e., the sealing glass powder of the present invention.

[0056] Example 6

[0057] (1) The following raw materials in weight percentage are mixed and ground uniformly in a mortar: 60% SiO2, 35% B2O3, 1.5% Al2O3, 0% ZnO, 2% Li2O, 0.25% Na2O, 0.25% K2O, 0.5% Cr2O3, 0.4% BaO, and 0.1% CaF2.

[0058] (2) The mixed glass raw materials are placed in a corundum crucible, the corundum crucible is sent into a muffle furnace and kept at 1550° C. for 1 hour, and the molten glass liquid is poured into a double-roll cold rolling mill to obtain a glass sheet.

[0059] (3) Place the glass piece in a sealed sample preparation crusher and crush it for 1 minute to obtain coarse glass powder.

[0060] (4) Mix 100% glass coarse powder and 0% silica powder in a mortar, and put them into a ball mill. The mass ratio of the powder to zirconium oxide balls and anhydrous ethanol is 1:4:4. The mixture is fully mixed and ball milled at a speed of 500 rpm for 3 hours. The ball-milled glass powder is placed in an oven and dried at 80°C for 24 hours to obtain dry glass fine powder, i.e., the sealing glass powder of the present invention.

[0061] Example 7

[0062] (1) The following raw materials in weight percentage are mixed and ground uniformly in a mortar: 60% SiO2, 35% B2O3, 1.5% Al2O3, 0% ZnO, 2% Li2O, 0.25% Na2O, 0.25% K2O, 0.5% Cr2O3, 0.4% BaO, and 0.1% CaF2.

[0063] (2) The mixed glass raw materials are placed in a corundum crucible, the corundum crucible is sent into a muffle furnace and kept at 1550° C. for 1 hour, and the molten glass liquid is poured into a double-roll cold rolling mill to obtain a glass sheet.

[0064] (3) Place the glass piece in a sealed sample preparation crusher and crush it for 1 minute to obtain coarse glass powder.

[0065] (4) 80% by mass of coarse glass powder and 20% by mass of silica powder were mixed evenly in a mortar, and the mixture was placed in a ball mill with a mass ratio of powder to zirconium oxide balls and anhydrous ethanol of 1:4:4. The mixture was fully mixed and ball milled at a speed of 500 rpm for 3 hours. The ball-milled glass powder was placed in an oven and dried at 80°C for 24 hours to obtain dry glass fine powder, i.e., the sealing glass powder of the present invention.

[0066] Example 8

[0067] (1) The following raw materials in weight percentage are mixed and ground uniformly in a mortar: 58% SiO2, 38% B2O3, 1% Al2O3, 0% ZnO, 2% Li2O, 0% Na2O, 0% K2O, 0.5% Cr2O3, 0.4% BaO, and 0.1% CaF2.

[0068] (2) The mixed glass raw materials are placed in a corundum crucible, the corundum crucible is sent into a muffle furnace and kept at 1550° C. for 1 hour, and the molten glass liquid is poured into a double-roll cold rolling mill to obtain a glass sheet.

[0069] (3) Place the glass piece in a sealed sample preparation crusher and crush it for 1 minute to obtain coarse glass powder.

[0070] (4) 80% by mass of coarse glass powder and 20% by mass of silica powder were mixed evenly in a mortar, and the mixture was placed in a ball mill with a mass ratio of powder to zirconium oxide balls and anhydrous ethanol of 1:4:4. The mixture was fully mixed and ball milled at a speed of 500 rpm for 3 hours. The ball-milled glass powder was placed in an oven and dried at 80°C for 24 hours to obtain dry glass fine powder, i.e., the sealing glass powder of the present invention.

[0071] The present invention uses a precision impedance analyzer to test the dielectric constant of the sealing glass powder, granulates and presses the prepared sealing glass powder, sinters it at a suitable sealing temperature for the material according to a certain sealing process, and grinds it into a disc, and then tests the dielectric constant thereof.

[0072] The present invention adopts a precision impedance analyzer to test the dielectric loss of the sealing glass powder, granulates and compresses the prepared sealing glass powder, sinters it at a suitable sealing temperature for the material according to a certain sealing process and grinds it into a disc, and then performs a dielectric loss test on it.

[0073] Table 1

[0074] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 <![CDATA[SiO2]]> 65 65 65 65 65 60 60 58 <![CDATA[B2O3]]> 30 28 28 28 28 35 35 38 <![CDATA[Al2O3]]> 0.5 1.5 2 1.5 1.5 1.5 1.5 1 ZnO 0 0.5 1 0.5 0.5 0 0 0 <![CDATA[Li2O]]> 2.5 2 3 2 2 2 2 2 <![CDATA[Na2O]]> 0.5 1 0 1 1 0.25 0.25 0 <![CDATA[K2O]]> 0.5 1 0 1 1 0.25 0.25 0 <![CDATA[Cr2O3]]> 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 BaO 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 <![CDATA[CaF2]]> 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1

[0075] Table 2

[0076] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Glass powder (wt%) 100 95 90 85 80 100 80 80 Silica powder (wt%) 0 5 10 15 20 0 20 20 Dielectric constant (1MHz) 5.04 5.12 5.10 4.95 4.88 4.66 4.43 4.09 Dielectric loss (1MHz) 0.00238 0.00317 0.00444 0.00248 0.00244 0.00561 0.00125 0.00142

Claims

1. A sealing glass powder with low dielectric constant and dielectric loss, characterized in that: The sealing glass powder includes 80% to 100% borosilicate glass powder and 0% to 20% silica powder in terms of mass percentage; the borosilicate glass powder includes 56% to 65% SiO2, 26% to 40% B2O3, 0% to 2% Al2O3, 0% to 2% ZnO, 2% to 3% Li2O, 0% to 1.5% Na2O, 0% to 1.5% K2O, 0.5% to 1% Cr2O3, 0% to 0.5% BaO, and 0% to 0.5% CaF2 in terms of mass percentage.

2. A method for preparing the sealing glass powder with low dielectric constant and dielectric loss according to claim 1, characterized in that: The method is: (1) Mix and grind all the raw materials of borosilicate glass powder in a mortar until they are uniformly mixed; (2) placing the mixed raw materials in a corundum crucible, placing the corundum crucible in a muffle furnace and keeping the temperature at 1500-1550° C. for 1-2 hours, pouring the molten glass into a double-roll cold rolling mill to obtain a glass sheet; (3) Place the glass piece in a sealed sample preparation crusher and crush it for 1 to 2 minutes to obtain a coarse glass powder; (4) 80% to 100% glass coarse powder and 0% to 20% silica powder are mixed in a mortar, ethanol is added, and the mixture is placed in a ball mill. The mixture is fully mixed and ball milled at a speed of 500 rpm for 3 hours. The ball-milled glass powder is placed in an oven and dried at 80° C. for 24 hours to obtain a sealing glass powder.

3. The method for preparing a sealing glass powder with low dielectric constant and dielectric loss according to claim 2, characterized in that: In step (4), the mass ratio of powder to zirconium oxide balls and anhydrous ethanol is 1:4:4.

Citation Information

Patent Citations

  • Low-dielectric constant low-dielectric loss glass

    CN108975689A

  • Low dielectric constant glass powder and preparation method thereof

    CN109399937A

  • Sealing glass powder for radio frequency connector and preparation and sealing methods thereof

    CN115724589A

  • Composite glass granulation powder for kovar alloy sealing and preparation method thereof

    CN116768483A

  • Leadless phosphate seal glass and its preparation method

    CN1830856A